Review on Stress Tolerance in Campylobacter jejuni - Kim, Se-Hun; Chelliah, Ramachandran; Ramakrishnan, Sudha Rani; Perumal, Ayyappasamy Sudalaiyadum; Bang, Woo-Suk; Rubab, Momna; Daliri, Eric Banan-Mwine; Barathikannan, Kaliyan; Elahi, Fazle; Park, Eunji; Jo, Hyeon Yeong; Hwang, Su-Bin; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Campylobacter spp. are the leading global cause of bacterial colon infections in humans. Enteropathogens are subjected to several stress conditions in the host colon, food complexes, and the environment. Species of the genus Campylobacter, in collective interactions with certain enteropathogens, can manage and survive such stress conditions. The stress-adaptation mechanisms of Campylobacter spp. diverge from other enteropathogenic bacteria, such as Escherichia coli, Salmonella enterica serovar Typhi, S. enterica ser. Paratyphi, S. enterica ser. Typhimurium, and species of the genera Klebsiella and Shigella. This review summarizes the different mechanisms of various stress-adaptive factors on the basis of species diversity in Campylobacter, including their response to various stress conditions that enhance their ability to survive on different types of food and in adverse environmental conditions. Understanding how these stress adaptation mechanisms in Campylobacter, and other enteric bacteria, are used to overcome various challenging environments facilitates the fight against resistance mechanisms in Campylobacter spp., and aids the development of novel therapeutics to control Campylobacter in both veterinary and human populations.